Open-Label Randomized Clinical Trial of Atropine Bolus Injection Versus Incremental Boluses Plus Infusion for Organophosphate Poisoning in Bangladesh - Abedin, M; Sayeed, A; Basher, A; Maude, R; Hoque, G; Faiz, M (2012)
Severe organophosphate compound (OPC) poisoning is an important clinical problem in many countries of the world. Unfortunately, little clinical research has been performed and little evidence exists with which to determine the best therapy. A study was therefore undertaken to determine the optimal dosing regimen for atropine in the treatment of OPC poisoning. An open-label randomized clinical trial was conducted in Chittagong Medical College Hospital, Chittagong, Bangladesh, on 156 hospitalized individuals with OPC poisoning from June to September 2006. The aim was to compare the efficacy and safety of conventional bolus doses with individualized incremental doses of atropine for atropinization followed by continuous atropine infusion for management of OPC poisoning. Inclusion criteria were patients with a clear history of OPC poisoning with clear clinical signs of toxicity, i. e. features of cholinergic crisis. The patients were observed for at least 96 h. Immediate outcome and complications were recorded. Out of 156 patients, 81 patients received conventional bolus dose atropine (group A) and 75 patients received rapidly incremental doses of atropine followed by infusion (group B). The mortality in group 'A' was 22. 5% (18/80) and in group 'B' 8% (6/75) (p<0. 05). The mean duration of atropinization in group 'A' was 151. 74 min compared to 23. 90 min for group 'B' (p<0. 001). More patients in group A experienced atropine toxicity than in group 'B' (28. 4% versus 12. 0%, p<0. 05); intermediate syndrome was more common in group 'A' than in group 'B' (13. 6% versus 4%, p<0. 05), and respiratory support was required more often for patients in group 'A' than in group 'B' (24. 7% versus 8%, p<0. 05). Rapid incremental dose atropinization followed by atropine infusion reduces mortality and morbidity from OPC poisoning and shortens the length of hospital stay and recovery. Incremental atropine and infusion should become the treatment of choice for OPC poisoning. Given the paucity of existing evidence, further clinical studies should be performed to determine the optimal dosing regimen of atropine that most rapidly and safely achieves atropinization in these patients. © 2012 American College of Medical Toxicology.